ECG Wave-Maven: Self-Assessment Program for Students and Clinicians (Out of Print) - Ary Goldberger (Association of American Medical Colleges, 2006)
Abstract Proficiency in electrocardiogram (ECG) interpretation is an essential skill for medical students, house staff, and clinicians. However, medical school and postgraduate resources to develop and upgrade the necessary high level of ECG literacy are severely limited. Furthermore, current textbook and classroom instructional materials do not adequately integrate ECG interpretation into specific contexts where waveform findings must be correlated with other clinical data. ECG Wave-Maven is a self-assessment program with multimedia adjuncts intended for students and clinicians. Users can select cases from a large list and view the corresponding ECGs in either quiz mode (multiple-choice quiz question with no answer showing) or reference mode (multiple-choice quiz question with answer showing). By creating the infrastructure for this unique web-based tutorial, we have begun to address the limitations in traditional approaches to ECG pedagogy.